Effects of sand fixation forest restoration on soil water infiltration capacity in Mu Us Sandy Land - Xin, Wang; Fucang, Qin; Zhenqi, Yang; Jianying, Guo; Li, Zhen (Frontiers in Plant Science, 2026)
IntroductionThe Mu Us Sandy Land has severe soil erosion and a fragile ecological environment. The construction of sand fixation forests has markedly increased vegetation coverage. However, water resource scarcity constrains the sustainable development of the ecosystem. Hence, an urgent challenge is to maintain construction of sand fixation forests while mitigating the high soil-water consumption.MethodsThe research selected sand fixation forests of the same recovery years, natural grassland and unrestored bare land for fixed-interval monitoring of soil moisture, together with measurements of vegetation features, soil physical properties, and water-holding and infiltration experiments for each hydrological layer.ResultsMajor findings: (1) Pinus sylvestris (PS) sand fixation forests had the greatest integrated water-holding capacity, 1.25 times that of bare land. (2) The effective soil-moisture supply depths were 40 cm, 150 cm, 150 cm and 100 cm for Gressland (GL), Salix cheilophila (SC) , PS and Bare land (BL). After the moisture supply, PS showed a large water consumption. From the standpoint of conserving soil moisture, GL was the optimal vegetation type, followed by SC. (3) WHC had a direct, significant negative effect on soil water content (SWC) (p < 0.05); WHC also negatively influenced the initial infiltration rate (IIR); and IIR directly influenced SWC. Results further show that canopy and litter layers of sand fixation forests can replenish soil moisture by altering WHC and IIR, but the high water consumption of trees still keeps SWC at low levels.DiscussionTherefore, based on comprehensive consideration of sand fixation needs and water conservation, Salix cheilophila (SC) performs better in water holding and infiltration promotion, and is more suitable for construction of sand fixation forests in this region. In water-lack areas, shrub-grass mixed forests should be considered for construction of sand fixation forests in the future.